Exploring the clinical effects of Andrographis paniculata-derived compounds, its extract, or derivatives for the treatment of COVID-19: a systematic review and meta-analysis - Prabhakornritta, Peerapong; Waranuch, Neti; Fuangchan, Anjana; Srikham, Kantapich; Boonpattharatthiti, Kansak; Barnig, Cindy; Boonyasuppayakorn, Siwaporn; Pitaksuteepong, Tasana; Bhattarakosol, Parvapan; Moulari, Brice; Pellequer, Yann; Dhippayom, Teerapon (Frontiers in Pharmacology, 2025)
The COVID-19 pandemic created a global health crisis, with limited effective treatments. Andrographis paniculata (Burm. f.) Nees (AP), with known anti-inflammatory and antiviral properties, has been explored as adjunctive therapy for COVID-19, but its clinical evidence remains inconclusive. We hypothesized that AP-derived compounds may improve symptoms and inflammatory responses in mild-to-moderate COVID-19. This systematic review and meta-analysis aimed to evaluate the clinical and biological effects of AP-derived compounds, its extract (APE), or its derivatives in patients with mild-to-moderate COVID-19. A systematic search was conducted in PubMed, EMBASE, CENTRAL, and EBSCO Open Dissertations from January 2020 to October 2024. Randomized controlled trials (RCTs) examining the effects of single-herb AP products compared to antivirals or supportive care (SC) in patients with mild-to-moderate COVID-19 were included if they reported clinical recovery, fever or cough resolution, C-reactive protein (CRP), or interleukin-6 (IL-6) levels. Risk of bias (RoB) was assessed using Cochrane RoB 2.0. A random-effects model was used to estimate pooled effects of included trials, expressed as relative risk (RR) and mean difference (MD) with 95% confidence intervals (CIs). Six RCTs involving 660 adults aged 18 to 60 were included. Compared to antivirals or SC, single-herb AP products showed no significant improvements in fever resolution (RR 1.12; 95%CI 0.90 to 1.38; I2 = 0.0%) or cough resolution (RR 0.98; 95%CI 0.74 to 1.31; I2 = 47.0%). No significant differences were observed in serum CRP (MD -0.04; 95%CI -0.26 to 0.18; I2 = 0.0%) and IL-6 levels (MD -0.07; 95%CI -0.17 to 0.03; I2 = 0.0%). While some studies not included in the meta-analysis suggested early reductions in CRP and IL-6, the findings were inconsistent. RoB was high for fever resolution but low for biomarkers. Mild adverse events, primarily liver enzyme elevations, resolved without severe complications. Our systematic review and meta-analysis suggest a potential role for AP extract and its derivatives as adjunctive therapy for COVID-19, with trends indicating possible benefits in symptom improvement and inflammation reduction. These findings highlight the need for further research to explore AP as a complementary therapeutic strategy in COVID-19 management.Systematic Review Registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD42024608858, identifier CRD42024608858.